Training about english jargon tourism in the Al-Hidayah teaching group of Pantai Cermin district Serdang Bedagai district - Loebis, Roma Ayuni A.; Syaifuddin; Alimansyar; Dirmanyah; Arfianty, Rani (Talenta Publisher, 2019)
Mirror Beach is one of the potential tourist areas in Serdang Bedagai Regency. As the tourism area is synonymous with tourism, the community service activity in this proposal is to develop English-language tourism jargon in the Al-Hidayah recitation group in Pantai Cermin District, Serdang Bedagai District. Al-Hidayah Study Group consists of mothers who live around the tourist destination, Pantai Cermin. As one of the tourist destinations, this location is often visited by foreign tourists. The mothers who are included in this study group are dominant traders who sell around the beach. However, their ability to communicate in English is still minimal. This is due to the lack of understanding of English and the limited vocabulary in English so that they have difficulty communicating in English. The final goal to be achieved in this service is to increase the ability of mothers to communicate using English. The solution offered is to teach English-language tourism jargon so that their vocabulary increases. And also teaching about simple English so they can use it in daily communication. With increasing vocabulary and understanding of English, it is hoped that they will increase their competence and confidence.